Consumption of Pornographic Materials among Hong Kong Early Adolescents: A Replication - Daniel T. L. Shek; Cecilia M. S. Ma (The Scientific World Journal)
Consumption of pornographic materials was examined in 3,638 secondary 2 students in Hong Kong. Results showed that over 80% of the respondents had never consumed pornographic materials in the past year. Internet pornography was the most common medium that adolescents used when viewing pornographic materials. Males reported a higher level of pornography consumption than did females. Participants who were born in mainland China were more likely to consume pornographic materials than their Hong Kong counterparts. Regardless of the types of pornographic materials, the levels of pornography consumption significantly increased over time. Results also showed that higher levels of positive youth development and better family functioning were concurrently related to a lower level of pornography consumption at secondary 2. The relative contribution of positive youth development and family factors to pornographic material consumption was also explored.